2018
DOI: 10.3390/app8122602
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Douglas-Fir Lumber Properties: Comparison between a Benchtop Near-Infrared Spectrometer and Hyperspectral Imaging System

Abstract: Near-infrared (NIR) spectroscopy and NIR hyperspectral imaging (NIR-HSI) were compared for the rapid estimation of physical and mechanical properties of No. 2 visual grade 2 × 4 (38.1 mm by 88.9 mm) Douglas-fir structural lumber. In total, 390 lumber samples were acquired from four mills in North America and destructively tested through bending. From each piece of lumber, a 25-mm length block was cut to collect diffuse reflectance NIR spectra and hyperspectral images. Calibrations for the specific gravity (SG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Visible and near infrared (Vis-NIR) spectroscopy has been widely used in many sectors, including the food, material, and life sciences [7][8][9]. In the field of forestry, many studies have demonstrated its potential to determine components, such as moisture, density, lignin content, and so on; detect wood preservation; and classify species [10][11][12][13][14][15][16]. Sandak et al applied cluster analysis (CA) and principal component analysis (PCA) to classify powdered samples (fraction < 0.5 mm) and wood samples, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near infrared (Vis-NIR) spectroscopy has been widely used in many sectors, including the food, material, and life sciences [7][8][9]. In the field of forestry, many studies have demonstrated its potential to determine components, such as moisture, density, lignin content, and so on; detect wood preservation; and classify species [10][11][12][13][14][15][16]. Sandak et al applied cluster analysis (CA) and principal component analysis (PCA) to classify powdered samples (fraction < 0.5 mm) and wood samples, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Following the measurements described in [51], a radial arm saw was used to cut a block (38 mm × 89 mm × 51 mm longitudinally) from each piece of lumber for NIRS and HSI analysis. Only 390 blocks (Canada-88, Idaho-95, Oregon-109, Washington-98) were available (utilized in [18]). From the 390 blocks, a subsample of 100 was selected for this study with the aim of capturing the full range of values for MOE and SG and equally representing the different sampling locations.…”
Section: Specimen Preparation and Testingmentioning
confidence: 99%
“…It has been demonstrated that the spectral data provided by NIR-HSI and SWIR-HSI could produce wood property calibrations whose performance was equivalent to those obtained using a benchtop NIR spectrometer [18,23]. These results are encouraging although, even with recent developments in HSI technology, hyperspectral cameras typically record fewer wavelengths (i.e., spectral sampling interval-SSI) compared to NIR benchtop spectrometers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, distribution maps obtained using hyperspectral imaging techniques are now widely used in agricultural studies, forestry, meat quality testing, etc. [26][27][28][29]. Meanwhile, the use of hyperspectral imaging techniques for generating soil TAs concentration distribution maps using machine learning models remains to be studied [30].…”
Section: Introductionmentioning
confidence: 99%